The Role of Entrepreneurship Education, Role Models, and Perceived Behavioural Control in Enhancing Entrepreneurial Motivation - Nikmah, Filda Khoirun; Gumintang, Bagas; Widiastuti, Ekaningtyas; Aryanto, Ronald (Amkop Management Accounting Review (AMAR), 2025)
Entrepreneurship in higher education is implemented to produce competitive graduates ready to work. Entrepreneurial motivation is crucial for translating entrepreneurial intentions into action. This study aims to examine the influence of entrepreneurship education, role models, and perceived behavioural control on entrepreneurial motivation. Data collection methods included questionnaires and interviews. The sampling technique used was convenience sampling. The study found that entrepreneurship education and role models did not influence entrepreneurial motivation, whereas perceived behavioural control did. The findings of this study are expected to motivate students to be brave and independent in starting and running a business despite the various risks involved.